Effect of polymer type on the properties of polypropylene composites with high loads of spent coffee grounds - Marques, Mariana (2022)
The main focus of this work is to study the processability and characteristics of highly loaded spent coffee grounds (SCG) thermoplastic polymer composites, for sustainable applications. SCG powder was characterized in terms of size distribution, moisture, morphology and thermal stability. Polymer/SCG composites were prepared by extrusion compounding. Polypropylene (PP) homopolymer and copolymer were used as the polymeric matrix. Upon compounding by extrusion composites were injection moulded and characterized for its physical, morphological and mechanical properties in order to determine the effect of polymer type and filler content. Morphological characteristics of the composites were investigated using optical microscopy and SEM analysis. The results for PP homopolymer showed little deterioration of the mechanical properties when using the highest SCG load. In the case of PP homopolymer, the greatest variations occurred when increasing from 0 to 20 %. With higher SCG loads, the measured properties changed little. PP copolymer showed a more continuous pattern of properties decay with increasing SCG load, especially for tensile strength, elongation at break and impact strength. Regarding PP copolymer, with maximum SCG load, the tensile strength decreased from 26.8 GPa (neat PP) to 10.8 GPa, the elongation at break showed a drop of more than 95 %, while the Young's modulus increased from 800 MPa to 1160 MPa. This research work has shown that SCG can be used as fillers in the preparation of environmentally friendly composites with SCG load up to 60 wt% thus contributing to the reuse of waste generated by the coffee industry.